PARADIGM FOR CONTEMPORARY SYMBOLIC REALITY - Elena Korableva (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Objective: Civilization development in its concrete historical specificity is embodied in symbolic forms that require interpretation and understanding of its meaning. Info communication symbolic reality sets new parameters of self-determination rights, creates a new type of information behavior. Adequate entry into the modern social context requires analysis of the basic concepts of symbolic reality of human existence, and its contemporary sound. The dialectical materialist methodology allows us to investigate human immersion in contradictive meanings of the era, the skills of interaction with the increased flow of information, the ability to determine information needs and use this information right way as well as the ability to analyze this information. Scientific novelty is reflected in axiological evolutionary approach to the analysis of reproduction in the sign and symbol of the spiritual and the practical forms of human multidimensional realities of their existence in their specific historical context. Conclusions: 1) Persons' immersion into the space of cultural and historical symbolic processes determines the content of their socialization which is a process of self-identification in the symbolic reality, the process of entering the subject-shaped field of human culture; 2) An adequate model of signs and symbols reflects the diversity of information flows, that is the synthesis of a specific objective and true knowledge, its interpretation and value. Herewith, a lot of interpretations, pluralism and diversity of axiological points of view to understanding objective reality are obvious; 3) The use of signs becomes like a code or the language for communication between people. The interpretation of clip-culture determines the adequacy and efficiency of action based on the identified meanings and values of diverse information and communication symbolic reality.